Examining the Role of Domain‐General Skills in Mathematics Learning and Intervention Response in Kindergarten. Issue 4 (23rd October 2021) - Shanley, Lina; Clarke, Ben; Smolkowski, Keith; Doabler, Christian T.; Kurtz‐Nelson, Evangeline C.; Fien, Hank
Abstract: Effective early mathematics instruction is critical to support long‐term mathematics achievement. Given that student response to typical instruction varies, a range of mathematics interventions have been developed to support foundational mathematics development. However, not all students respond to these interventions. To better understand factors associated with intervention response, the current study explored how domain general cognitive skills were associated with intervention response for 621 kindergarten students with or at risk for mathematics difficulties. Results indicated that although domain general skills were associated with mathematics achievement, there was no evidence of differential response to intervention based on cognitive skills. When examining differences while holding initial mathematics skill constant, there was a non‐significant, but potentially important pattern of students with higher domain general skills demonstrating greater mathematics gains as a result of intervention participation. Implications for mathematics intervention and curriculum development, including potentially impactful instructional approaches and cognitive scaffolds are discussed.